Device-measured physical activity and cardiovascular disease risk in adolescent childhood cancer survivors. A physical activity in childhood cancer survivors (PACCS) study - Bratteteig, Mari; Anderssen, Sigmund Alfred; Rueegg, Corina Silvia; Ruud, Ellen; Torsvik, Ingrid Kristin; Kriemler, Susi; Grydeland, May (Frontiers in Pediatrics, 2022)
Objectives We aimed to compare cardiovascular disease (CVD) risk factors in childhood cancer survivors (CCS) with age- and sex-stratified reference material and examine the association between physical activity (PA) intensities and CVD risk factors in CCS. Materials and methods Within the cross-sectional, multicenter Physical Activity in Childhood Cancer Survivors (PACCS) study, we collected data on CVD risk factors [VO2–peak (mL⋅kg–1⋅min–1), body mass index (BMI, kg/m2), systolic blood pressure (SBP, mmHg), and total-cholesterol/HDL-cholesterol (Total/HDL)] among CCS aged 9–18 years. CVD risk factors were compared to references with immediate t-tests. We transformed CVD risk factors into z-scores based on international references and generated an individual CVD risk score: [inverse ZVO2–peak + ZBMI + ZSBP + ZTotal/HDL)/4]. Multivariable mixed linear regression models were used to analyze the associations between device-measured PA intensities and CVD risk factors. Results We included 157 CCS aged on average 13.4 years at inclusion and 8.2 years from diagnosis. Male CCS had lower VO2–peak compared to references (45.4 vs. 49.4 mL⋅kg–1⋅min–1, P = 0.001), higher diastolic BP (67 vs. 63 mmHg, P < 0.001), lower HDL (1.35 vs. 1.44 mmol/L, P = 0.012), as well as a tendency to higher CVD risk score (z-score=0.14 vs. 0.00, P = .075). Female CCS’ CVD risk factors were comparable to references. Vigorous-intensity PA (VPA) was associated with CVD risk factors. A 10-min increase in VPA was associated with higher VO2–peak (β = 4.9, 95% CI, 2.1–7.7), lower Total/HDL (β = −0.3, 95% CI, −0.6 to −0.1) and a lower CVD risk score (β = −0.4, 95% CI, −0.6 to −0.2). Conclusion Male adolescent CCS had less favorable values of CVD risk factors compared to references. VPA in adolescent CCS is associated with clinically meaningful favorable values of CVD risk factors.